'L'homosexualité? ça n'existe pas en banlieue': the indigènes de la république and gay marriage, between intersectionality and homophobia. (3rd April 2019) - Lotem, Itay
ABSTRACT: Since its founding in 2005, the anti-racist organisation Les Indigènes de la République has acquired a certain notoriety in the French public eye as a fresh voice of the anti-racist Left. The Indigènes combined postcolonial and intersectional analysis with more traditional forms of anti-racist activism. This article examines how the Indigènes engaged with LGBTQ minorities as they tried to articulate 'intersectional' views of the Republic. While the intersection of gender and race was central to the emergence of the organisation in 2004, the Indigènes have mostly avoided addressing issues relevant to the LGBTQ communities. The one exception to this rule occurred in the wake of the Marriage pour tous protests against the legalisation of same-sex marriage, where the organisation equated 'homosexual identity' with colonial oppression. Using interviews and publication material, this article explores the gestation of the Indigènes' position on the issue of same-sex marriage, with its contradictions between a left-wing discourse that prioritised an idea of social justice through inclusion of all oppressed minorities and the desire to represent a marginalised constituency that was often unsympathetic to LGBTQ issues. Their choice highlights the difficulties of analysing the volatile political reality in contemporary France through abstract notions of social justice.